1991
DOI: 10.1111/j.1476-5381.1991.tb12463.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of the rodenticide, brodifacoum, on blood coagulation and vitamin K metabolism in rats

Abstract: The long‐term (30 days) effects of a single dose of brodifacoum (0.2 mg kg−1, orally) on blood clotting activity and on liver parameters of the vitamin K cycle were investigated in rats. Maximal effect on blood clotting activity was seen on day one. On day seven blood clotting activity had returned to normal. Liver microsomal vitamin KO reductase activity was maximally suppressed (10% of control activity) on day one, steadily recovered to about 40% on day 15 to remain at that level. The same time course was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
2
27
1
Order By: Relevance
“…Mosterd and Thijssen (1991) reported that brodifacoum rapidly accumulated in the liver and the liver content on day 30 was not different from day 7 after a single oral dose of 0.2 mg/kg bw to rats, which is well in accordance with our results in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Mosterd and Thijssen (1991) reported that brodifacoum rapidly accumulated in the liver and the liver content on day 30 was not different from day 7 after a single oral dose of 0.2 mg/kg bw to rats, which is well in accordance with our results in mice.…”
Section: Discussionsupporting
confidence: 92%
“…In the rat at least 70% of the hepatic reductase has to be inhibited before comprising the clotting factor synthesis (Mosterd & Thijssen, 1992). Overcapacity of the vitamin K epoxide reductase probably also exists in man (Mosterd & Thijssen, 1991).…”
Section: Discljssionmentioning
confidence: 99%
“…It is possible dose is not important above a threshold level adequate to reduce blood clotting. Eason et al (1996) demonstrated that possum blood-clotting time began increasing 2 days after brodifacoum treatment, but was only significantly higher than pretreatment values after 7 days, whereas clotting time peaks within 24 h in rats (Mosterd and Thijssen 1991). If the biochemical response duration (Fig.…”
Section: Discussionmentioning
confidence: 92%